Assessing Groundwater Dynamics and Hydrological Processes in the Sand River Deposits of the Limpopo River, Mozambique - Saveca, Paulo Sérgio Lourenço; Abi, Attoumane; Stigter, Tibor Yvan; Lukas, Eelco; Fourie, Francois (Frontiers in Water, 2022)
Drought and water scarcity constrain the socioeconomic development of most (semi-)arid regions in the Limpopo River Basin. Due to climate variability and significant water withdrawals upstream, the Limpopo River is no longer perennial in Mozambique. This research aims to assess the groundwater hydrodynamics and hydrochemistry of the Limpopo sand river, and its potential as an alternative water source in the Limpopo River Basin. Several field investigations were carried out in the Limpopo Sand river near Chókwè and Guijá, such as groundwater level monitoring, infiltration tests, 2D geoelectrical surveying, water sampling for chemical analysis (major ions), stable isotopes analysis (2H and 18O) and sediment analysis. The sand river lithological profiles of the study area show the dominance of unconsolidated sediments composed of medium to coarse sand, underlain by clay and silt formations. Electrical resistivity tomography surveys, together with deeper drillings reveal sand thicknesses that can reach 10–15 m in the valley, reduced to 2-5 m in the main river channel. During the dry season the groundwater provides base flow to the river and the average water level drop in the sand river system is about 1.8 m, remaining saturated thicknesses of 5m. Connectivity with the river margins is limited, due to the clayey nature of the river bank sediment, but local paleochannels and point bars can result in a continuation of sand layers away from the river channel. Analysis of the Limpopo River water level shows that large parts of sand river areas are flooded almost every year, providing optimal conditions for recurring recharge of the system of the wider river valley through lateral flow and vertical infiltration fed by surface runoff. Estimated storage revealed large potential for abstraction and the recharge of the sand river is very rapid (confirmed by infiltration tests) and water flows through the sand river at high velocities (depending on the hydraulic gradient). Isotope analysis combined with chemical analysis revealed an interaction between groundwater in the sand river system and the surface water. Hydrological processes controlling the water quality are evaporation and to a minor extent mineral dissolution, with the groundwater being of Ca-HCO3 type.